Efforts to Improve Student Learning Motivation in Mathematics Learning by Using the Realistic Mathematics Education Approach at MIN 1 Banda Aceh - Lubis, Azmil Hasan (ETNOPEDAGOGI: Jurnal Pendidikan dan Kebudayaan, 2025)
This study aims to explore the effectiveness of the Realistic Mathematics Education (RME) approach in enhancing student learning motivation in mathematics at MIN 1 Banda Aceh. Low motivation among students in mathematics learning has been a persistent challenge, often resulting in decreased engagement and suboptimal learning outcomes. To address this issue, a Classroom Action Research (CAR) was conducted over two cycles, each consisting of planning, action, observation, and reflection phases. The participants were 28 fourth-grade students who exhibited varying levels of interest and performance in mathematics. The RME approach, which emphasizes contextual learning and the use of real-life situations to make abstract mathematical concepts more relatable, was implemented through a series of structured learning activities. Data collection methods included observation, student motivation questionnaires, interviews, and documentation. The results demonstrated a significant increase in students' motivation, as evidenced by higher participation rates, improved attitudes towards mathematics, and greater enthusiasm during classroom discussions and group activities. Quantitative analysis showed an increase in the average motivation score from 63.2% in the pre-cycle to 78.5% in the first cycle, and further to 89.4% in the second cycle. Qualitative findings supported these results, revealing that students were more actively involved, collaborative, and confident in solving mathematical problems when learning was linked to real-world contexts. In conclusion, the Realistic Mathematics Education approach proved to be an effective pedagogical strategy for improving student learning motivation in mathematics. It is recommended that educators adopt RME principles to create meaningful and engaging learning experiences that resonate with students’ everyday lives. Future research may explore the long-term impact of RME on students' academic achievement and its adaptability across different educational settings.